Strengthening Human Resources Development and Supporting the Establishment of a Quality Assurance Programme for the Use of Ionizing Radiation in Diagnostic and Therapeutic Applications - AMOUSSOU GUENOU, KUASSI MARCELLIN (My University, 2018)
Benin's capacities in the field of medical physics are very limited. As a result, the equipment emitting ionizing radiation and radioactive sources used for diagnostic and therapeutic purposes in health centres and hospitals has never been calibrated or characterized after its installation, with the consequence that the exposure of patients and other persons occupationally affected by radiation is poorly controlled. The project aims to develop a strategic and operational planning programme for the quality assurance of radiation-emitting devices and radioactive sources used in the health sector, with a view to ensuring that optimal doses are delivered to patients and used for medical purposes in diagnostic and therapeutic applications. The country also lacks of an adequate pool of well-trained human resources in the areas of Nuclear Medicine and Radiotherapy, whereas additional human resources are needed in Diagnostic Imaging. Benin is investing national resources to provide adequate health services to its population. national programmes focus for example on cancer prevention, surveillance, early diagnosis, screening, treatment and palliative care, all following WHO and IAEA guidelines. Actions are required to improve the operation and performance of this programme. To maximize the impact of effective diagnosis, the strategy to create a nuclear medicine centre remains a priority, with the adoption of an integrated approach under the national health programmes. The creation of a national centre for advanced diagnostics and radiotherapy, which should also include a radiotherapy service, remains a priority. The main objectives of this centre will be to provide an environment where better treatment can be offered on site to more patients, reduce significantly the costs of medical evacuation, improve cancer research and training and establish a network for continuity of care. During the national discussions on health held in November 2007, special emphasis was placed on the creation of a national centre for advanced diagnostics and radiotherapy that would be home to a nuclear medicine service, a radiotherapy service and a chemotherapy service, among others. The centre’s main objectives will be to provide an environment where better treatment can be offered on site to more patients, significantly reduce medical evacuation outlays, offer more appropriate training for health professionals and establish a network for continuity of care. The establishment of this centre, which is part of the Ministry of Health’s programme of public investments for 2015–2017, will be accomplished by a public–private partnership, based on feasibility studies conducted with IAEA support. Construction works are in currently in progress. The Government of Benin also wishes to address other challenges such as long-term support for the continuing education programme for health professionals and the creation of education and outreach programmes for civil society. Linkage with the National Health Development Plan and the National Contingency Plan: Recognizing that there are shortcomings detracting from the quality of care in public hospitals, the Ministry of Health has set development of the hospital subsector as a priority subprogramme in the made provision in the 2009–2018 National Health Development Plan. Good quality care also requires the proper use of diagnostic and treatment tools such as the X-ray machines used in hospitals. Health pyramid The Beninese health system has a pyramidal structure which reflects the country’s territorial divisions. It comprises three levels: • the central or national level, which is administered by the Minister of Health, who ensures the implementation of the health policy crafted by the government; health activities at this level are carried out in the university hospitals, of which there are currently eight in service; • the intermediate or departmental level, which is administered by the departmental directors of health. Health services at this level are administered in the district hospitals, which currently number four; • the peripheral or operational level: this comprises the country’s different health zones, of which there are 34, distributed across the entire area of Benin. Health zones are the most decentralized of the health system’s operational entities. They comprise a network of initial contact public services (maternity wards, clinics in remote areas and health centres) and private health care structures supported by a public or private first reference hospital, known as a zone hospital, and are designed to cover areas with a population of between 100 000 and 200 000. Each health zone covers one to four communes and there is a zonal hospital in each health zone. Currently, of the planned 34 health zones, 28 – or 82.35% – are in operation. Regarding the incidence in hospitals, the average is reported at 115.1/year, whereas the incidence of the five main cancers is reported at 5285/year.